PENERAPAN MODEL INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PELAJARAN IPS KELAS IV MIN 8 ACEH BARAT - Andhika, M. Rezki; Setiawan, Andra (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2022)
Lack of active student interaction in learning such as joint discussions between students and teachers, as well as the lack of application of learning models that can support student activity. The learning outcomes of fourth grade students of MIN 8 West Aceh can be seen from the low level of student learning outcomes. The research target is how teacher activities, student activities and student learning outcomes through the application of the Index Card Match model on Theme 5 My Heroes in Class IV MIN 8 West Aceh. This study aims to describe teacher activities, student activities, and student learning outcomes during learning. The research instruments used in this study were teacher activity observation sheets, student activity observation sheets, and test question sheets. In this study, researchers used Classroom Action Research (CAR) which was carried out in the classroom by using an action to improve the quality of the learning process in order to obtain better learning outcomes than before. The data analysis technique used is using the percentage formula. Based on observations of teacher activity in the first cycle, the percentage was 73% (good), and in the second cycle it increased to 90% (very good). Meanwhile, student activity in the first cycle obtained a percentage of 72% (good) and the second cycle increased to 84% (very good). While the student learning outcomes obtained in the first cycle only 12 students who completed with a value of 60% and who did not complete 11 students with a value of 40%. While in the second cycle there was an increase, namely 20 students achieved completeness with a score of 86% and 3 students did not complete with a score of 14%. Based on the results of data analysis, it can be obtained that the use of the Index Card Match learning model can improve student learning outcomes.